Elucidating the Structural Composition of an Fe–N–C Catalyst by Nuclear‐ and Electron‐Resonance Techniques. (9th June 2019) - Wagner, Stephan; Auerbach, Hendrik; Tait, Claudia E.; Martinaiou, Ioanna; Kumar, Shyam C. N.; Kübel, Christian; Sergeev, Ilya; Wille, Hans‐Christian; Behrends, Jan; Wolny, Juliusz A.; Schünemann, Volker; Kramm, Ulrike I.
Abstract: Fe–N–C catalysts are very promising materials for fuel cells and metal–air batteries. This work gives fundamental insights into the structural composition of an Fe–N–C catalyst and highlights the importance of an in‐depth characterization. By nuclear‐ and electron‐resonance techniques, we are able to show that even after mild pyrolysis and acid leaching, the catalyst contains considerable fractions of α‐iron and, surprisingly, iron oxide. Our work makes it questionable to what extent FeN4 sites can be present in Fe–N–C catalysts prepared by pyrolysis at 900 °C and above. The simulation of the iron partial density of phonon states enables the identification of three FeN4 species in our catalyst, one of them comprising a sixfold coordination with end‐on bonded oxygen as one of the axial ligands. Abstract : Ein Fe‐N‐C‐Katalysator wurde mit Kern‐ und Elektronenresonanztechniken analysiert. Die Ergebnisse zeigen, dass selbst nach milder Pyrolyse und Säurebehandlung noch signifikante Anteile an α‐Eisen und Eisenoxid vorhanden sind. Es stellt sich die Frage, inwieweit bei Pyrolysetemperaturen von 900 °C oder höher tatsächlich noch FeN4 ‐Zentren, die die aktiven Zentren in der Sauerstoffreduktionsreaktion sind, in Fe‐N‐C‐Katalysatoren vorhanden sein können.